Effects of fasting on isolated murine skeletal muscle contractile function during acute hypoxia. - Cameron A Schmidt (Public Library of Science (PLoS), 2020)
Stored muscle carbohydrate supply and energetic efficiency constrain muscle functional capacity during exercise and are influenced by common physiological variables (e.g. age, diet, and physical activity level). Whether these constraints affect overall functional capacity or the timing of muscle energetic failure during acute hypoxia is not known. We interrogated skeletal muscle contractile properties in two anatomically distinct rodent hindlimb muscles that have well characterized differences in energetic efficiency (locomotory- extensor digitorum longus (EDL) and postural- soleus muscles) following a 24 hour fasting period that resulted in substantially reduced muscle carbohydrate supply. 180 mins of acute hypoxia resulted in complete energetic failure in all muscles tested, indicated by: loss of force production, substantial reductions in total adenosine nucleotide pool intermediates, and increased adenosine nucleotide degradation product-inosine monophosphate (IMP). These changes occurred in the absence of apparent myofiber structural damage assessed histologically by both transverse section and whole mount. Fasting and the associated reduction of the available intracellular carbohydrate pool (~50% decrease in skeletal muscle) did not significantly alter the timing to muscle functional impairment or affect the overall force/work capacities of either muscle type. Fasting resulted in greater passive tension development in both muscle types, which may have implications for the design of pre-clinical studies involving optimal timing of reperfusion or administration of precision therapeutics.